Urinary Biomarkers in Interstitial Cystitis/Bladder Pain Syndrome and Its Impact on Therapeutic Outcome - Hung-Yu Lin; Jian-He Lu; Shu-Mien Chuang; Kuang-Shun Chueh; Tai-Jui Juan; Yi-Chang Liu; Yung-Shun Juan (Diagnostics, 2021)
Interstitial cystitis/bladder pain syndrome (IC/BPS) is defined as a chronic bladder disorder with suprapubic pain (pelvic pain) and pressure and/or discomfort related to bladder filling accompanied by lower urinary tract symptoms, such as urinary frequency and urgency without urinary tract infection (UTI) lasting for at least 6 weeks. IC/BPS presents significant bladder pain and frequency urgency symptoms with unknown etiology, and it is without a widely accepted standard in diagnosis. Patients’ pathological features through cystoscopy and histologic features of bladder biopsy determine the presence or absence of Hunner lesions. IC/PBS is categorized into Hunner (ulcerative) type IC/BPS (HIC/BPS) or non-Hunner (nonulcerative) type IC/BPS (NHIC/BPS). The pathophysiology of IC/BPS is composed of multiple possible factors, such as chronic inflammation, autoimmune disorders, neurogenic hyperactivity, urothelial defects, abnormal angiogenesis, oxidative stress, and exogenous urine substances, which play a crucial role in the pathophysiology of IC/BPS. Abnormal expressions of several urine and serum specimens, including growth factor, methylhistamine, glycoprotein, chemokine and cytokines, might be useful as biomarkers for IC/BPS diagnosis. Further studies to identify the key molecules in IC/BPS will help to improve the efficacy of treatment and identify biomarkers of the disease. In this review, we discuss the potential medical therapy and assessment of therapeutic outcome with urinary biomarkers for IC/BPS.